2022
DOI: 10.3389/fimmu.2022.933360
|View full text |Cite
|
Sign up to set email alerts
|

Autoreactive B cells recruited to lungs by silica exposure contribute to local autoantibody production in autoimmune-prone BXSB and B cell receptor transgenic mice

Abstract: Occupational exposure to inhaled crystalline silica dust (cSiO2) is linked to systemic lupus erythematosus, rheumatoid arthritis, systemic sclerosis, and anti-neutrophil cytoplasmic autoantibody vasculitis. Each disease has a characteristic autoantibody profile used in diagnosis and implicated in pathogenesis. A role for cSiO2 in modulating humoral autoimmunity in vivo is supported by findings in mice, where respirable cSiO2 induces ectopic lymphoid structures as well as inflammation in exposed lungs across ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…A comparison with human LN gene expression revealed similar up-regulated genes as observed during the development of murine LN and TLS (50). In animal models, TLS formation was associated with the development of systemic autoimmune disease (65) and with local autoantibody production (66). A timed exposure to an environmental trigger allowed the investigators to assess a temporal evolution of TLS in lupus.…”
Section: Evidence For the Formation Of Tls In Lnmentioning
confidence: 70%
“…A comparison with human LN gene expression revealed similar up-regulated genes as observed during the development of murine LN and TLS (50). In animal models, TLS formation was associated with the development of systemic autoimmune disease (65) and with local autoantibody production (66). A timed exposure to an environmental trigger allowed the investigators to assess a temporal evolution of TLS in lupus.…”
Section: Evidence For the Formation Of Tls In Lnmentioning
confidence: 70%
“…These B cells exhibit aberrant regulation, escaping from normal tolerance mechanisms and demonstrating a propensity to produce autoantibodies. The study observed as well an increase in anti-DNA and antimyeloperoxidase (MPO) immunoglobulins in cultures of Toll-like receptor ligand-stimulated lung cells derived from BXSB mice exposed to silica [16].…”
Section: Mechanism Of Silica Induced Autoimmune Disordersmentioning
confidence: 96%